Speed PID controller simulation of a reaction wheel for CubeSat orientation applications. Issue 1 (January 2021) - Medina, I; Santiago, L; Hernández-Gómez, J J; Castillo, R; Couder-Castañeda, C
Abstract: CubeSat technology is a low-cost alternative for space research in universities worldwide, promoting research areas in tele-detection, Earth and space observation, telecommunications, meteorology, etc. In this sense, Attitude and Determination Control Subsystem (ADCS) plays a key role in order to achieve a fast and precise orientation of the satellite, aiding the system by acquiring the specific and critical angles they require to accomplish the space mission. Therefore, choosing adequate actuators is key for the correct manipulation of the CubeSat, and it must consider size, weight and electrical power usage limitations of the CubeSat Standard. ADCS actuators must generate a quick response to generate an active momentum that modifies the satellite attitude. This work proposes a speed PID controller for a reaction wheel using low-cost materials for its implementation in 1U CubeSats.